162k views
5 votes
22) -6:6(-2 – h) + 3 + j; use h=3, and j = 6

User Prasham
by
4.4k points

1 Answer

5 votes

Answer

The answer is -27

Explanation

-6 + 6(-2 - h) + 3 + j;

use h=3, and j = 6

We can simply put in the values for h and j in the expression and then simplify it.

-6 + 6(-2 - h) + 3 + j

-6 + 6(-2 - 3) + 3 + 6

We then simplify this expression using the normal rules of simplification (PEMDAS)

-6 + 6(-2 - 3) + 3 + 6

Solving the expression in the bracket first

-2 - 3 = -5

The expression becomes

-6 + 6(-5) + 3 + 6

We then take care of 6(-5) which is 6 multiplied by -5 and is equal to -30

The expression becomes

-6 + (-30) + 3 + 6

= -6 - 30 + 3 + 6

= -36 + 9

= - 27

Hope this Helps!!!

User Art Haedike
by
4.8k points